Synthesis of sensitizer containing triphenylamine as donor group and investigation of solar cell applicability - Kilicarslan, Fatma Aytan (YILDIZ TECHNICAL UNIV, 2025)
Developing technology and the increase in the world population increase the need for energy day by day. Renewable energy sources provide an affordable, eco-friendly way to meet this need. Solar energy, which is a renewable energy source, has sufficient capacity to obtain more affordable and clean energy compared to other sources. Researchers are interested in triphenylamine and its derivatives because of their numerous uses in solar cells, electronics, and medicine. This study, solar cell applicability was investigated by synthesizing an organic dye, in which the dye contains triphenylamine as the donor group and the hydroxyl group as the acceptor group that provides binding to TiO2. FTIR, MS, NMR, and UV-Vis spectroscopy are used to identify the compound's (srl-2) structure. With srl-2-based DSSC and AM (amplitude modulation) irradiation (100 mW/cm2), a PCE (photoelectric conversion efficiency) value of 0.01% was attained.
Keywords: Dye-Sensitized Organic Solar Cells (Dsscs); Renewable Energy Sources; Triphenylamine; PHOTOPHYSICAL PROPERTIES; ANCHORING GROUPS; DYES; Engineering